Evaluating the effectiveness of an autism-specific public transport app for individuals on the autism spectrum: a pilot study. (4th July 2022) - Rezae, Mortaza; McMeekin, David; Tan, Tele; Krishna, Aneesh; Lee, Hoe
Abstract: Purpose: Autism is characterised by differences in social skills, limited communication abilities and repetitive behaviour, which often result in increased reliance on other people. Transportation is but one task that is commonly burdened on family members. Public transport is an inexpensive and widely available form of travel which facilitates independence. However, it presents unique challenges for individuals on the spectrum, as it requires complex skills including, but not limited to, understanding abstract information (e.g., maps, service schedules, etc.), problem-solving unexpected situations and timely management of transfers. As such, most individuals on the autism spectrum do not use public transport and have never considered using it. Here we evaluate the effectiveness of an autism-specific public transport app, OrienTrip, with autistic individuals and allied health professionals. Methods: A total of 16 individuals on the autism spectrum (eight male and eight female participants) and 22 allied health professionals (19 females and three male participants) were recruited for the pilot study. Results: We found that OrienTrip is effective in facilitating public transport use for autistic individuals. Individuals on the autism spectrum expressed their satisfaction with the app and agreed that it makes public transport easy to use. Similarly, allied health professionals also indicated that OrienTrip is helpful in assisting autistic individuals use public transport safely. Conclusion: Our findings demonstrate that OrienTrip can be used to facilitate independent travel for individuals on the autism spectrum using public transport. This can improve community participation opportunities for autistic individuals, including enhanced education, employment and social outcomes. Implications for rehabilitation: Individuals on the autism spectrum heavily rely on other people, namely family members, for their transportation needs. Public transport is an inexpensive and widely available form of travel which facilitates independence; however, it presents unique challenges for autistic individuals, as such, most individuals do not use it or consider using it. In this research, we have developed and evaluated one of the first autism-specific public transport mobile apps that facilitates independent public transport use. This tool can improve community participation opportunities for autistic individuals, including enhanced education, employment and social outcomes.